Shadow Economy Effects on Quality of Life - Zahra Nasrollahi; Azam rezaei; Frnaz Dehghan Banadkoki (اقتصاد باثبات)
One of the components of the economy of all countries is the shadow economy, given the hidden secrecy of this sector of the economy from the point of view of economic policymakers, it can lead to a distortion of the correctness of the state of the economy, the imposition of false policies, and the reduction of the impact of economic policies. Therefore, one of the concerns of policy makers is to identify the size of this sector and to use strategies to reduce the size and control the impact of this sector on overall performance and other sectors of the economy. Among the variables that the shadow economy has a significant impact on is the quality of life. The shadow economy, on the one hand, has a positive impact on increasing employment and income, and on the other hand, due to non-compliance with occupational and safety standards, has a negative impact on the quality of work life, health, safety and so on. Therefore, the main issue of this research is the impact of shadow economy on quality of life. In this research, structural modeling and multiple-cause multiple-index causes are used to estimate the amount of underground economics and its evolution and its effect on quality of life. The results suggest a positive impact of the shadow economy on the quality of life.